In Search of Autoethnography of Female Ulama: An Alternative Approach to the Study of Islamic Family Law - Wardatun, Atun; Abdul Wahid (Universitas Islam Internasional Indonesia, 2023)
Autoethnography is a method of qualitative inquiry that reveals the personal experiences of an individual in relation to social phenomena as a source of knowledge. Despite criticism of its subjectivities, many disciplines have widely used this approach but it is still rarely employed in Islamic Family Law (IFL). As a guide that regulates the relations of family members in the most important social institution, family law is very close to the lives of both sexes, male and female. Unfortunately, IFL is seen as suffering from gender inequality due to imbalanced gender authorities or male-centered characteristics. This article explores the works of three Indonesian female ulama – Musdah Mulia, Badriyah Fayumi, and Nina Nurmila – which are relevant to issues surrounding IFL to provide answers to the following questions: How are IFL issues – particularly in public and private spheres, ideal husband-wife relations, and women’s domestication – represented in female ulama’s works? Why should the autoethnography approach be incorporated into their works? After reviewing the female ulama's publications, this article maps different approaches and methods they have used in discussing the above IFL issues. It argues that an autoethnographic approach must still be present or visible from their extensive works. This approach allows for a better understanding of the deeper aspects of family life, which is private and intimate. This article, therefore, proposes that autoethnography should be a significant part of female ulama’s future works and that utilizing this approach to reformulate IFL based on the ulama’s personal, reflexive, and analytical accounts of family issues will contribute to more transformative and emancipatory Islamic Family Laws.